Criaç\~ao, destruiç\~ao e rotatividade do emprego formal no setor privado Brasileiro (1997-2012) - Gílson Geraldino Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper analyzes the job creation, job destruction and job turnover in the Brazilian private sector between 1997 and 2012 as proposed by Davis and Haltiwanger (1992), with particular attention to fluctuations after the 2008 financial crisis. This crisis is considered an adverse shock in the world economy with potential effects to Brazil. The econometric evidence indicates that 1) job net creation and employee turnover are procyclical and job destruction countercyclical, as expected, 2) throughout the period the effect of fluctuations on the job creation, job destruction and job turnover is even for establishments in and out of the sample and for establishments which were, and 3) the post-2008 effect is not only distinguished these two groups as the post-2008 positive effect on establishments that were in the sample but was insufficient to offset the post-2008 negative effect on establishments in and out of the sample.
Keywords: J21; J45; J82; 330; labor market; formal employment; private sector; exogenous adverse shock